An RRx-001 Analogue With Potent Anti-NLRP3 Inflammasome Activity but Without High-Energy Nitro Functional Groups - Lin, Hualong; Yang, Mingyang; Li, Cong; Lin, Bolong; Deng, Xianming; He, Hongbin; Zhou, Rongbin (Frontiers in Pharmacology, 2022)
NLRP3 inflammasome is involved in the pathology of multiple human inflammatory diseases but there are still no clinically available medications targeting the NLRP3 inflammasome. We have previously identified RRx-001 as a highly selective and potent NLRP3 inhibitor, however, it contains high-energy nitro functional groups and might cause potential processing problems and generates highly toxic oxidants. Here, we show that compound 149-01, an RRx-001 analogue without high-energy nitro functional groups, is a potent, specific and covalent NLRP3 inhibitor. Mechanistically, 149-01 binds directly to cysteine 409 of NLRP3 to block the NEK7-NLRP3 interaction, thereby preventing NLRP3 inflammasome complex assembly and activation. Furthermore, treatment with 149-01 effectively alleviate the severity of several inflammatory diseases in mice, including LPS-induced systemic inflammation, MSU-induced peritonitis and experimental autoimmune encephalomyelitis (EAE). Thus, our results indicate that 149-01 is a potential lead for developing therapeutic agent for NLRP3-related inflammatory diseases.